PENGARUH MOTIVASI, LINGKUNGAN DAN DISIPLIN TERHADAP KEPUASAN KERJA PADA TENAGA PENGAJAR YAYASAN PERGURUAN SETIA BUDI ABADI PERBAUNGAN - Siagian, Hanny; Erlin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine whether there is an influence of work motivation, work environment, and work discipline on job satisfaction in the teaching staff of the Setia Budi Abadi Perbaungan College Foundation. This research is a quantitative study using a questionnaire that analyzed with the SPSS 25 tool. The sample collection technique used the saturated sampling method with a total sample of 88 respondents. The data analysis method used is multiple linear regression analysis with statistical hypothesis testing. The simultaneous test results (F-test) showed that there was an influence of work motivation, work environment, and work discipline on the job satisfaction of the teaching staff, then through partial testing (T-test), the test results showed that there was an influence variable of work motivation and work discipline on the job satisfaction of teaching staff. While the work environment variable does not affect on the job satisfaction of the teaching staff. Adjusted r Square indicates that the variables of work motivation, work environment, and work discipline have an effect of around 66.80%, there is Job Satisfaction and the remaining 33.20% is explained by other variables not examined in this research.